2-face viewable liquid crystal display using 2-domain vertically aligned cell - Chen, Chao Ping; Chung, Te-Chen; Jen, Tean-Sen (Photonics Letters of Poland, 2011)
We propose a solution for obtaining a 2-face viewable liquid crystal display (LCD) that is able to show different images on the same screen depending on the viewing perspectives. Without requirement for any extra optical component, this function is simply realized by a 2-domain vertically aligned (VA) liquid crystal (LC) cell, which can accommodate two distinct viewing cones in its own right. Full text: PDF References: C. P. Chen, C. G. Jhun, T.-H. Yoon, and J. C. Kim, "Viewing Angle Switching of Tristate Liquid Crystal Display", Jpn. J. Appl. Phys. 46, L676 (2007). [CrossRef] C. P. Chen, C. G. Jhun, T.-H. Yoon and J. C. Kim, "Optimal design of omni-directional viewing angle switching panel", Opt. Express 15, 17937 (2007). [CrossRef] J.-I. Baek, Y.-H. Kwon, J. C. Kim, and T.-H. Yoon, "Dual-mode switching of a liquid crystal panel for viewing angle control", Appl. Phys. Lett. 90, 101104 (2007). [CrossRef] C. P. Chen, K.-H. Kim, T.-H. Yoon, and J. C. Kim, "A Viewing Angle Switching Panel Using Guest?Host Liquid Crystal", Jpn. J. Appl. Phys. 48, 062401 (2009). [CrossRef] C. P. Chen, J. H. Lee, T.-H. Yoon, and J. C. Kim, "Monoview/dual-view switchable liquid crystal display", Opt. Lett. 34, 2222 (2009). [CrossRef] D. J. Montgomery and M. Khazova, US patent 6859256 (2005). H. Ren and S.-T. Wu, "Adaptive liquid crystal lens with large focal length tunability", Opt. Express 14, 11292 (2006). [CrossRef] C. W. Wu, "Joint time delay and frequency estimation via state-space realization", IEEE Signal Proc. Lett. 10, 225 (2003). [CrossRef] Y. Qiao, T.-C. Chung, X. Huang, L. Zhou, Y.-W. Chiu, C.-T. Liao, T.-S. Jen, and D. Zhang, "A Novel Push-Pull VA Technology for High Performance LCD-TV", SID Symp. Dig. Tech. Pap. 41, 830 (2010). [CrossRef] P. K. Son, B. K. Jo, J. C. Kim, T.-H. Yoon, S. J. Rho, S. T. Shin, J. S. Kim, S. K. Lim, and J. H. Souk, , "Multi Domain Alignment of Liquid Crystals on Silicon Oxide Film Surfaces through Ion Beam Exposure", Jpn. J. Appl. Phys. 47, 8476 (2008). [CrossRef] K. Hanaoka, Y. Nakanishi, Y. Inoue, S. Tanuma, Y. Koike, and K. Okamoto, "A New MVA-LCD by Polymer Sustained Alignment Technology", SID Symp. Dig. Tech. Pap. 35, 1200 (2004). [CrossRef] T. Ishinabe, T. Miyashita, and T. Uchida, "Wide-Viewing-Angle Polarizer with a Large Wavelength Range", Jpn. J. Appl. Phys. 41, 4553 (2002). [CrossRef] Y.-J. Wu, Y.-S. Jeng, P.-C. Yeh, C.-J. Hu, and W.-M. Huang, "Stereoscopic 3D Display Using Patterned Retarder", SID Symp. Dig. Tech. Pap. 39, 260 (2008). [CrossRef] V. Chigrinov, E. Prudnikova, K. W. Ng, and H. S. Kwok, "Non Polarizer Guest?Host mode based on Dyes with Negative Dichroism", Jpn. J. Appl. Phys. 42, 1297 (2003). [CrossRef]